The first conspiracy : the secret plot to kill George Washington - Meltzer, Brad; Mensch, Josh (New York, NY : Flatiron Books, 2019)
"In 1776, an elite group of soldiers were handpicked to serve as George Washington's bodyguards. Washington trusted and relied on them, but unbeknownst to him, some of the guards were part of a treasonous plan. In the early months of the Revolutionary War, these traitorous soldiers, along with the Governor of New York and Mayor of New York City, launched a deadly scheme against the most important member of the military: George Washington himself. This is the story of the secret plot against George Washington and how it was revealed. It is a story of leaders, liars, counterfeiters, and jailhouse confessors. It also shows just how difficult the battle was for George Washington--and how close America was to losing the war. Taking place during the most critical period of our nation's birth, [this book] tells a remarkable and little-known piece of American history. The story not only reveals George Washington's character and leadership in the face of seemingly insurmountable odds against British forces but also illuminates the origins of America's counterintelligence agencies"--
Map on endpaper.
Includes bibliographical references (pages 365-399) and index.
Keywords: Washington, George, -- 1732-1799 -- Assassination attempt, 1776.; United States. -- Continental Army. -- Commander-in-Chief's Guard; Attempted assassination -- United States; Treason -- United States; United States -- History -- Revolution, 1775-1783 -- Secret service; United States -- History -- Revolution, 1775-1783 -- Military intelligence